2012
DOI: 10.1088/0029-5515/52/9/094010
|View full text |Cite
|
Sign up to set email alerts
|

Study of fast-ion transport induced by fishbones on JET

Abstract: Abstract. The impact of fishbone oscillations onto a confined fast ion population is simulated for a JET plasma and benchmarked against experiment quantitatively with the help of neutron rate measurements. The transient drops in volume integrated neutron emission are found to be mainly caused by the spatial redistribution of the (neutral beam injected) fast ion population confined in the plasma rather than by fast ion loss. The simulations yield a quadratic dependence of the neutron drop on the fishbone amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…In addition to sawtooth events, we highlight that fishbone instabilities also appear in this discharge at times close to some of the sawtooth crashes. These modes represent another manifestation of an (m, n) = (1, 1) perturbation in the plasma and can, under certain conditions, also give rise to significant anomalous fast-ion transport [22,23]. An example is presented in figure 7, showing the burst-like rise and slightly slower decay of magnetic perturbations characteristic of these modes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to sawtooth events, we highlight that fishbone instabilities also appear in this discharge at times close to some of the sawtooth crashes. These modes represent another manifestation of an (m, n) = (1, 1) perturbation in the plasma and can, under certain conditions, also give rise to significant anomalous fast-ion transport [22,23]. An example is presented in figure 7, showing the burst-like rise and slightly slower decay of magnetic perturbations characteristic of these modes.…”
Section: Resultsmentioning
confidence: 99%
“…Strong and coherent fast-ion losses observed in the presence of neoclassical tearing modes have shown that these modes selectively redistribute fast particles under resonance conditions [59,78]. Fishbones [72,79] and off-axis fishbones [80] have also been demonstrated to act selectively in velocity space. However, the underlying mechanisms leading to enhanced fast-ion transport in the presence of these MHD instabilities are still not understood well.…”
Section: Discussionmentioning
confidence: 99%
“…Note that here we define EPMs to be fast-particle-driven internal kink modes with a dominant poloidal mode number m = 1, and with fundamental toroidal mode number n = 1; higher toroidal harmonics may also be present. Fast-ion transport induced by fishbones has recently been reported on JET, where the observed changes in neutron rate were compared with modelling [7]. Finally, on MAST, the recentlycommissioned collimated neutron camera has been used to detect changes in the radial emissivity profile of neutrons caused by sawteeth and EPMs [8].…”
Section: Introductionmentioning
confidence: 99%